Molecular hybridization: A useful tool in the design of new drug prototypes - Viegas-Junior, Cláudio [UNESP]; Danuello, Amanda [UNESP]; Bolzani, Vanderlan da Silva [UNESP]; Barreiro, Eliezer J.; Fraga, Carlos Alberto M. (Bentham Science Publishers, 2007)
Molecular hybridization is a new concept in drug design and development based on the combination of pharmacophoric moieties of different bioactive substances to produce a new hyrid compound with improved affinity and efficacy, when compared to the parent drugs. Additionally, this strategy can results in compounds presenting modified selectivity profile, different and/or dual modes of action and reduced undesired side effects. So, in this described several example of different strategies for drug design, discovery and pharmacomodulation focused on new innovative hybrid compounds presenting analgesic, anti-inflammatory, platelet anti-aggregating, anti-infections, anticancer, cardio- and neuroactive properties.
Keywords: Drug design; Hybrid compounds; Molecular hybridization; Pharmacophoric group combination; 1,2,3,11a tetrahydro 8 hydroxy 7 methoxy 5h pyrrolo[2,1 c][1,4]benzodiazepin 5 one; 1h 1,2,4 oxadiazolo[4,3 a]quinoxalin 1 one; acetylsalicylic acid; agmatine; alpha tocopherol; analgesic agent; anthramycin; antiinfective agent; antiinflammatory agent; antineoplastic agent; antithrombocytic agent; benzocaine; ciprofloxacin; dipyrone; distamycin A; dolastatin; geldanamycin; lidocaine; losartan; metoclopramide; mitiglinide; nateglinide; norfloxacin; procainamide; propranolol; sparfloxacin; taltobulin; unindexed drug; uramustine; zatebradine; analgesia; antiarrhythmic activity; antiinflammatory activity; antimicrobial activity; antineoplastic activity; antioxidant activity; binding affinity; blood pressure regulation; drug design; drug efficacy; drug mechanism; drug research; drug selectivity; drug structure; human; molecular hybridization; nonhuman; pharmacophore; review; smooth muscle relaxation; structure activity relation; thrombocyte aggregation inhibition; vasodilatation; Analgesics; Animals; Anti-Infective Agents; Anti-Inflammatory Agents, Non-Steroidal; Antineoplastic Agents; Cardiovascular Agents; Drug Design; Fibrinolytic Agents; Humans; Hypoglycemic Agents; Ligands